Efficacy and Safety of PARP Inhibitor Combination Therapy in Recurrent Ovarian Cancer: A Systematic Review and Meta-Analysis - Ren, Ning; Zhang, Leyin; Yu, Jieru; Guan, Siqi; Dai, Xinyang; Sun, Leitao; Ying, Minli (Frontiers in Oncology, 2021)
Objectives. Though it is known to all that PARP inhibitors (PARPis) are effective when used as maintenance alone for women with recurrent ovarian cancer (ROC), little is known about whether to use them in combination with other drugs would contribute to a better efficacy. We performed a systematic review and meta-analysis to explore the efficacy and safety of PARPi combination therapy compared with monotherapy. Materials and Methods. We searched for randomized controlled trials (RCTs) that offered the date we needed in Pubmed, Embase, Cochrane and major conference. Data extraction and processing were completed by three investigators to compare OS, PFS and ORR both in intervention and control subset. Then, we calculated the pooled RR and 95% CI of all-grade and high-grade adverse effects to study its safety. And we evaluated the within-study heterogeneity by using subgroup and sensitivity analysis. Results and Conclusion. A total of 3 eligible RCTs covering 343 women were included. In PFS analysis, PARP inhibitor (PARPi) combination therapy can significantly improve PFS for women with ROC when compared with the controls (HR:0.46, 95% CI, 0.35 to 0.59), especially for those with mutated-BRCA (HR:0.29, 95% CI, 0.19 to 0.45). And in OS analysis, combination therapy is not inferior to monotherapy (HR:0.90, 95% CI, 0.50 to 1.61). As for ORR, the effectiveness of combination therapy and monotherapy was almost the same (RR: 1.04, 95% CI, 0.82 to 1.31). Additionally, combination therapy seldom causes more adverse events, both in all-grade or high grade.